The Failing Firm Defence in US and EU Competition Law – A Comparative and Diachronic Analysis - Koivuniemi, Henrik (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis deals with the so-called failing firm defence in the merger control regimes of the United States and the European Union. According to the failing firm doctrine, an otherwise anticompetitive merger may be cleared if one of the merging parties is a failing firm which is likely to be forced out of the market in the absence of the merger. The doctrine requires the fulfillment of three criteria, which have to do with the firm’s financial failure, absence of alternative purchasers, as well as the exit of the firm’s assets from the relevant market. The thesis is an instance of traditional doctrinal research, although it contains ingredients of comparative law and legal history as well. In addition, the thesis utilizes especially economic literature dealing with the prediction of financial failure. The thesis has three broad research objectives. The first research objective is to trace in detail the doctrine’s origins and subsequent course of development (the diachronic objective). In light of this development, it will be observed how the doctrine’s rationale has changed from the minimization of social costs associated with corporate bankruptcy to the promotion of allocative efficiency, especially via the retention of the failing firm’s productive assets in the relevant market. The second research objective is to examine the salient differences in the formulation and application of the doctrine between the antitrust regimes of the United States and the European Union (the comparative objective). Alongside formal considerations, the comparison will also uncover differences in principles, which partially hark back to the different traditions of economic thought of the antitrust regimes in question. However, the differences reflect variations in emphasis, rather than categorical divergences of policy. The third research objective is to analyze the semantic content of each criterion of the doctrine in light of the relevant case law and academic discussion. On the basis of this analysis, suggestions for improving the doctrine will also be provided (the policy improvement objective). The foremost improvement advocated in the thesis involves a modification of the doctrine’s first criterion concerning financial failure, whereby application of the criterion should utilize formal methods developed in the field of economics for the prediction of financial failure. In particular, the thesis advocates the adoption of the so-called Altman Z-score model, which is found to correspond well with the legal standards established in the case law dealing with the failing firm doctrine.